PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN - Wahyuandari, Wenni (Program Doktor Ilmu Ekonomi, 2019)
Corporate Social Responsibility (CSR) is a concept that organizations, especially companies have a responsibility to employees, shareholders, the community and theenvironment, especially consumers, in all aspects of the company's operations, especiallyfor problems that affect the environment such as pollution, waste, product safety andlabor. Corporate Social Responsibility is no longer voluntary or a commitment made bythe company in taking responsibility for the company's activities, but rather becomes anobligation for the company to do or implement it. To evaluate the successful implementation of CSR and as a means of accountabilityto shareholders and investors, it is necessary to disclose social responsibility (CorporateSocial Disclosures) in the annual financial statements. CSD (Corporate SocialDisclosures) of the company can be described as the availability of financial informationin the form of financial and non-financial ratios which include social benefits and socialcosts related to the interaction of organizations with the physical environment and socialenvironment.Keyword : Corporate Social Responsibility, Corporate Social Disclosures, Financial Ratios